β-Dual Dari Ruang Barisan (N̅,Δλ) ∞ , (N̅,Δλ), Dan (N̅,Δλ) O - Salwa, Salwa; Aini, Qurratul; Switrayni, Ni Wayan (Jurnal Matematika; Vol 11 No 2 (2021)DO - 10.24843/JMAT.2021.v11.i02.p141, 2022)
Sequence s p aces is one of interesting to p ic of analysis research. Some of that are convergent and bounded sequence. In this p a p er we define some releated BK s p aces (N̅,Δλ) ∞, (N̅,Δλ), dan (N̅,Δλ)O some characteristics releated to them. Moreover we determine their β-dual.